A comparative study of early postoperative feeding versus conventional feeding for patients undergoing caesarean section - S., Neeraja; Reddy, Naritha; Fathima, Naima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Early alimentation after caesarean delivery probably has limited clinical significance in terms of improved energy and protein intake. Decreasing the post-operative ileus is possible with early feeding. Objective of this study was to study efficacy of early postoperative feeding versus conventional feeding for patients undergoing caesarean section. Methods: Present study was hospital based comparative study carried out among 200 women who fulfilled the selection criteria. The cases were divided into 2 groups of 100 each by suitable random sampling technique. Group A included 100 cases who were given early feeding within 6 hours of caesarean delivery. Group B included 100 control who were given the feeding after 24 hours of caesarean delivery. Results: The mean duration of postoperative hospital stay in Group A and Group B was 4.59±0.65 and 4.81±0.81 days respectively (p <0.05). The mean time to return of bowel sounds in Group A and Group B was 2.79±1.36 and 3.55±1.49 hours respectively (p <0.01). 2(2%) cases in group A had postoperative ileus symptoms, whereas 3 (3%) cases in Group B had the same. Statistically significant difference (p <0.05) was seen in terms of vomiting 1% versus 17%, nausea 5% versus 16%, abdominal distention 2% versus 7%, diarrhea 4% versus 90% in the early feeding versus conventional feeding groups. Conclusions: It can be concluded from present study that fast return to the normal diet is possible with early feeding among women undergoing cesarean section compared to the conventional feeding among women undergoing cesarean section.